The Analytic Conceptual Framework for Comprehending Factors Essential to Realize Sustainability in Rural Communitiesa Water Supply Systems (Global Journal of Human-Social Science, 2015)
This research study is an analytic conceptual framework aiming at understanding factors essential to obtain sustainability in rural communities' water supply systems. The basis of the study is on observations and desk-study or literature reviewing. Its aim is to determine factors necessary for obtaining sustainability in rural communities' water supply systems. The analytic review covers general conclusions in community participation in Rural Water System/RWS, perceptions of communities on underlying issues pertaining to sustainable management of Rural Water Supply System/RWSS and factors towards sustainability of RWSS. Illumination of these intensifies understanding of all aspects that contribute to sustainability in the topic of rural water supply or RWS. The study covers typologies of community participation in rural water supply, perceptions of community and sustainability and conceptual framework for sustainable rural water system services.
Keywords: 1 rural water supply; 2 community participation; 3 sustainable management; 4 sustainability; 5 rural communities